A relação entre composição corporal e desempenho funcional de pacientes pós COVID-19 atendidos em um ambulatório de saúde - (:unkn) unknown (UNIFAP - Universidade Federal do Amapá, 2023)
Introduction: Post-COVID-19 Syndrome is characterized by the persistence of symptoms and/or long-term complications in individuals who have recovered from the initial infection. This post-viral condition has significant impacts on the lives of these individuals, leading to substantial changes in their routine and daily activities. While there is evidence of possible short and long-term impacts on physical performance in recovered patients, understanding the modifications in the body structure of these individuals still lacks detailed information. Objectives: This study aims to analyze the relationship between body composition and functional performance in post-COVID-19 patients treated in a health outpatient clinic. Methodology: This is an analytical, cross-sectional, and prospective study conducted on patients who showed undetectable viral load after hospital discharge. Screening was performed to determine participant eligibility. Assessment instruments included sociodemographic data, clinical signs, symptomatic history during the infection period, functional tests of sitting and rising from a chair in 30 seconds, and the Time Up and Go test. Body composition assessment was conducted using a bioimpedance device. Data analysis was conducted using the statistical software BioStat, version 5.3, considering a significance level defined as p<0.05. Results: The study analyzed 25 patients, revealing a predominance of females (52%), with dyspnea being the most prevalent clinical sign (88%), and the most affected age group ranging between 40 and 69 years. A moderate correlation was observed in statistical analyses between the TUG and BIA variables (skeletal muscle mass with R2: 0,1971, fat-free mass with R2: 0,1744, lean mass with R2: 0,1747, and total body water with R2: 0. 0,1721). However, the correlation between the variables of the 30-second sit-to-stand test and BIA did not show statistically significant correlation (skeletal muscle mass with p value: 0.5746, fat-free mass with p value: 0.9692, lean mass with p value: 0.9956, and total body water with p value: 0.9869). Conclusion: The highlighted correlation between TUG and BIA underscores the importance of assessing body composition to effectively guide clinical evaluation, treatment, and individual recovery processes. Despite the absence of correlation between the 30-second sit-to-stand test and BIA, it is essential to consider emerging knowledge about post-infection sequelae, raising the possibility that other tests may have a more substantial relationship with body composition. This study not only contributes significantly but also expands the current understanding of the subject.
Keywords: Capacidade Física; Desempenho Funcional; Composição Corporal; COVID 19; CNPQ::CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL; ODS 3 – Saúde e bem-estar